2007
DOI: 10.1016/j.ijpara.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the subtelomeric regions of Giardia lamblia genome isolate WBC6

Abstract: Giardia trophozoites are polyploid and have five chromosomes. The chromosome homologues demonstrate considerable size heterogeneity due to variation in the subtelomeric regions. We used clones from the genome project with telomeric sequence at one end to identify six subtelomeric regions in addition to previously identified subtelomeric regions, to study the telomeric arrangement of the chromosomes. The subtelomeric regions included two retroposons, one retroposon pseudogene, and two vsp genes, in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…An exception is the hypervariable subtelomeric regions (as shown in Fig. 5) where sequences can vary within the same isolate and chromosome (Upcroft and Upcroft 1999;Prabhu et al 2007). A significant characteristic difference between WB and 106 is the 1.5-Mb chromosome 3/4 doublet in 106, whereas no such doublet is apparent in WB ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An exception is the hypervariable subtelomeric regions (as shown in Fig. 5) where sequences can vary within the same isolate and chromosome (Upcroft and Upcroft 1999;Prabhu et al 2007). A significant characteristic difference between WB and 106 is the 1.5-Mb chromosome 3/4 doublet in 106, whereas no such doublet is apparent in WB ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PFOR1 gene (clone G6/1 in the work of ) and C3/19 also belong to the same linkage group on chromosome 3/4 ( Fig. 2 Adam et al 1988;Yu et al 2002;Prabhu et al 2007) was mapped using NotI-cleaved DNA with NotI segments identified by chromosome 6-specific probes and the GiardiaDB. The positions and identity (letters F, A, etc.)…”
Section: Deletions From Ch991763mentioning
confidence: 99%
See 2 more Smart Citations
“…1995; Prabhu et al. 2007) and extremely small but with typical chromatin condensation levels (Tumova et al. 2015).…”
Section: Introductionmentioning
confidence: 99%